QUALITY ASSESSMENT OF URINE PRODUCED FROM FEMALE HILL CATTLE OF UTTARAKHAND - PATOO, R.A.; SINGH, D.V.; SINGH, S.K.; KAUSHAL, S.; SINGH, M.K. (Indian Journal of Animal Production and Management, 2017)
ABSTRACTCow urine has a unique place in Ayurveda and is suggested to improve generalhealth of human being. Indigenous and hill cattle have a good quality urine as comparedto crossbred cattle. So, present study was conducted utilizing primiparous lactating Hillcattle, Sahiwal and crossbred cattle maintained in Instructional Dairy Farm, GBPUAT,Pantnagar for comparing their urine constituents. Urine samples were collected earlymorning from four animals of each group at an interval of one month, with threerepetitions and were estimated for pH, specific gravity, total solid per cent, ash per cent,total protein, urea and creatinine. There was significant difference (Pdâ€0.05) betweenchemical composition of Hill cattle urine with that of Sahiwal and crossbred cattle urine.Lower pH, specific gravity, total solids, urea, creatinine, total protein, and ash per centwere observed in urine of Hill cattle while as higher values were observed in crossbredcattle urine. There was a non-significant difference (Pdâ€0.05) in urea, creatinine, totalprotein, and ash per cent among Hill cattle and Sahiwal urine but a significant difference(Pdâ€0.05) with crossbred cattle urine.Key words: Hill cattle, Sahiwal, Crossbred, Urine Composition, Uttarakhand